2019
DOI: 10.26442/00403660.2019.04.000211
|View full text |Cite
|
Sign up to set email alerts
|

Markers of dysbiosis in patients with ulcerative colitis and Crohn's disease

Abstract: The results of recent studies indicate a significant role of gut microbiota in the pathogenesis of inflammatory bowel diseases (IBD). The aim of the study was to study the taxonomic and functional composition of the gut microbiota in ulcerative colitis (UC) and Crohn's disease (CD) patients to identify key markers of dysbiosis in IBD. Materials and methods. Fecal samples obtained from 95 IBD patients (78 UC and 17 CD) as well as 96 healthy volunteers were used for whole-genome sequencing carried out on the SOL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 42 publications
5
33
1
1
Order By: Relevance
“…the number of Bacteroidetes and decrease in the number of Firmicutes [42]. However, in our study, on the contrary, we found a decrease in the level of Bacteroidetes on the 4 th week of the high-dose MB treatment (Fig 1A).…”
Section: Plos Onecontrasting
confidence: 81%
See 1 more Smart Citation
“…the number of Bacteroidetes and decrease in the number of Firmicutes [42]. However, in our study, on the contrary, we found a decrease in the level of Bacteroidetes on the 4 th week of the high-dose MB treatment (Fig 1A).…”
Section: Plos Onecontrasting
confidence: 81%
“…An increase in the level of bacteria of the genus Rodentibacter may indicate the presence of an infection [41]. Recently, Danilova et al [42] showed that the increase in the content of Proteobacteria in the microbiome is a marker of the development of inflammatory bowel disease (which includes Crohn's disease and ulcerative colitis). Other indicators of the of inflammatory bowel disease development are an increase in PLOS ONE…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, we found a signi cant ability of the genus Bilophila and Fusobacterium to selectively associate with cases of UC activity/remission. This agrees with the literature that describes a functional role for these bacteria in UC [64,65,66,67] and suggests its potential clinical bene t for an early identi cation of clinical-therapeutic phases of UC [68,69].…”
Section: Discussionsupporting
confidence: 91%
“…Microbial dysbiosis in UC is characterized by an increase of bacteria Proteobacteria and Bacteroidetes and a decrease of bacteria Firmicutes phylum and Euryarchaeota phylum. In addition, a decrease in the index of alpha diversity, the relative representation of bacteria producing butyrate, hydrogen; increase in relative representation of Ruminococcus was also reported (Danilova et al 2019).…”
Section: Discussionmentioning
confidence: 85%